The efficiency of the centralized system for delivery of specialized medical care to victims with acute spinal cord injury in a modern metropolis - Alexandr K. Dulaev; Vadim A. Manukovskiy; Denis I. Kutyanov; Sergey V. Iskrovskiy; Sergey L. Brizhan; Pavel V. Zhelnov; Natalya M. Dulaeva (Хирургия позвоночника, 2019)
Objective. To perform comparative assessment and identification of determinants of efficiency of the centralized system for delivery of specialized medical care to victims with acute spinal cord injury in the modern metropolis. Material and Methods. The results of specialized medical care delivered to 2283 victims with acute spinal cord injuries were studied. The comparison group (decentralized system: treatment in several multidisciplinary hospitals in St. Petersburg) included 306 patients, and study group (centralized system: treatment in a specialized urban center for emergency spinal surgery) – 1977. Comparative analysis of the results of surgical treatment included 44 patients from comparison group and 223 patients from the study group (p > 0.05). The methods of non-parametric statistics were used. Results. The centralized treatment system is characterized by a statistically significant increase in the rate of surgical activity, a manifold increase in the proportion of emergency spinal surgery (p < 0.01) and the mandatory use of modern technologies for surgical stabilization of the spine, shortening the hospital stay, as well as higher values of all indicators characterizing the results of treatment (p < 0.01). Conclusion. In a large city, the centralized system of treating victims with spinal cord injury is characterized by more efficient use of urban health resources and better treatment outcomes. The key to its successful creation and subsequent operation, in addition to the centralization of medical care with the reasonable formation and distribution of the incoming patient flow, adequate logistic support for the treatment process and the presence of highly qualified medical personnel, is the availability of modern surgical technologies in delivering specialized emergency care.